Biomarker toxicodynamics linked to BPA toxicokinetics in three-spined stickleback: a PBPK-TD model - Mit, Corentin; Bado-Nilles, Anne; Palluel, Olivier; Turiès, Cyril; Beaudouin, Rémy (HAL CCSD, 2022)
International audience Bisphenol A (BPA) is considered a substance of very serious concern due toits endocrine disruptor function, high production volume, and persistence in the aquaticenvironment. In this context, physiologically-based toxicokinetic models coupled withtoxicodynamics (PBTK-TD) have proven to be valuable tools. They allow proposingmore actual exposure scenarios as the exposure may vary over time and they alsoenable linking internal concentrations to various effects that are often decorrelated toexternal dose. Recently, a PBTK has been developed and adapted to BPA ADME(Absorption, Distribution, Metabolization, and Excretion) processes in the three-spinedstickleback. Thus, this work aimed to develop a PBTK-TD model that would permit tobetter understand the impact of BPA on the different functions of the fish, includingdefense capacities and reproduction. In particular, a precise knowledge of the internaldoses in the target organs would allow to i) clearly identify whether the transientbiomarker responses are linked to toxicokinetics, ii) identify the compounds (parentand/or metabolites) responsible for the biomarker responses, and iii) to identifynon-monotonic dose dependencies of biological responses to external exposures thatwould be non-monotonic. In detail, the PBTK was extended to include thetoxicodynamics of various biomarkers measured during two exposures to BPA, one ofseven-day exposure and seven-day depuration, and one of 21-day exposure.Biomarkers including non-specific cellular immunity, metabolic detoxification, oxidativestress, and reproductive parameters were analyzed to select a set of parametersvarying when exposed to BPA. Since it was supposed that the biomarker responseswere produced by indirect mechanisms, indirect toxicodynamic models were chosen todescribe the response. Consequently, mechanism-based equations describing theresponses of biomarkers over time were implemented in the existing PBTK specific toBPA. Then, TD data were divided into two sets, one to allow calibration ...